Distinct Clinical and Pathological Features of Melorheostosis Associated With Somatic MAP2K1 Mutations. (14th September 2018) - Jha, Smita; Fratzl‐Zelman, Nadja; Roschger, Paul; Papadakis, Georgios Z; Cowen, Edward W; Kang, Heeseog; Lehky, Tanya J; Alter, Katharine; Deng, Zuoming; Ivovic, Aleksandra; Flynn, Lauren; Reynolds, James C; et al.
ABSTRACT: Melorheostosis is a rare hyperostotic disease of the long bones classically characterized by a "dripping candle‐wax" radiographic appearance. We recently described somatic activating mutations in MAP2K1 as a cause of melorheostosis. Here, we report distinguishing characteristics of patients with MAP2K1 ‐positive melorheostosis. Fifteen unrelated patients with radiographic appearance of melorheostosis underwent paired biopsies of affected and unaffected bone for whole‐exome sequencing, histology, and cell culture. Eight patients with mutations in MAP2K1 in affected bone were compared to the seven MAP2K1 ‐negative patients to identify distinguishing characteristics. Patients with MAP2K1 ‐positive melorheostosis had a distinct phenotype with classic "dripping candle‐wax" appearance on radiographs ( p = 0.01), characteristic vascular lesions on skin overlying affected bone ( p = 0.01), and higher prevalence of extraosseous mineralization and joint involvement ( p = 0.04 for both). Melorheostotic bone from both MAP2K1 ‐positive and MAP2K1 ‐negative patients showed two zones of distinct morphology—an outer segment of parallel layers of primary lamellar bone and a deeper zone of intensely remodeled highly porous osteonal‐like bone. Affected bone from MAP2K1 ‐positive patients showed excessive osteoid ( p = 0.0012), increased number of osteoblasts ( p = 0.012) and osteoclasts ( p = 0.04), and increased vascularity on histology in comparison to paired unaffected bone which was not seen in affected bone in most MAP2K1 ‐negative patients. The identification of a distinct phenotype of patients with MAP2K1 ‐positive melorheostosis demonstrates clinical and genetic heterogeneity among patients with the disease. Further studies are needed to better understand the underlying pathophysiology and associated skin findings. © 2018 American Society for Bone and Mineral Research. Abstract : Patients with melorheostosis associated with somatic mosaic MAP2K1 mutations (found in affected bone and skin overlying affected bone) were more likely to have cutaneous vascular changes in skin overlying affected bone, classic "dripping candle‐wax appearance" on x‐rays and increased osteoid on bone histomorphometry. Presence of these characteristics may predict association with MAP2K1 mutations.